2021
DOI: 10.4103/ijdr.ijdr_654_19
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Histochemical Assessment of Root Resorption during Canine Retraction through Piezocision Site

Abstract: Introduction: The number of adult patients seeking orthodontics treatment has increased drastically. There is increased need for faster tooth movement and good esthetics. Piezocision is one of the methods used for accelerating the rate of tooth movement. Aims and Objectives: To assess the amount of root resorption after retraction of canine through piezocision site and compare it with that of recently extracted site using cone-beam computed tomography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Out of the 39 included studies, 33 were RCTs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], from which 17 had a split-mouth study design [ 34 , 37 , 41 , 45 , 48 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 62 , 64 , 65 , 66 ] and 6 were CCTs [ 22 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the 39 included studies, 33 were RCTs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], from which 17 had a split-mouth study design [ 34 , 37 , 41 , 45 , 48 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 62 , 64 , 65 , 66 ] and 6 were CCTs [ 22 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Using the Cochrane risk of bias tool, the risk of bias for the RCTs included in the current systematic review varied from low to high overall. Twelve studies had identified problems with the randomization practices [ 34 , 35 , 36 , 38 , 39 , 40 , 45 , 48 , 49 , 53 , 55 , 65 ]. Twenty-one of the thirty-three included RCTs with a sufficiently stated randomization process [ 37 , 41 , 42 , 43 , 44 , 46 , 47 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations